Administrative law penalties in financial activity - Cassagne, Juan Carlos (2020)
Phenomena such as the new constitutionalism, decriminalization and flexibilization of the legality principle have decisively contributed to the conception of Administrative law penalties. For this reason, this article seeks to define what these new trends imply, in order to transfer them to administrative criminal law. In this way, the legal nature of administrative criminal sanctions and the feasibility of applying the principles of criminal law in certain matters, especially in financial police, will be evaluated.Likewise, under this hypothesis, the sanctioning regime of financial activity in Argentina will be examined; to analyze the powers of its regulatory body (the Central Bank of the Argentine Republic), its sanctioning power and, finally, the legal nature of its sentences.